(untitled) - Ross, Frederick C. (London, 1986)
The authors present a basic and accessible introduction to the world of microbiology. In the first section, "Microbial Structure and Mode of Life," the structure and functioning of fungi, bacteria, and viruses are discussed (with particular attention paid to the description and discussion of their reproduction and nutrition). The second section, "Handling Microbes," introduces the methods used to culture, control, and study these organisms in the laboratory. The final section covers the "Isolation, Classification and Identification of Microbes." This book will be suitable as a basic text for undergraduate students of microbiology.
Keywords: Vi trùng học,Microbiology